Políticas públicas para a educação inclusiva: análise das diretrizes curriculares no município de Curitiba (2000-2009) - Kowalski, Beatriz Micaloski (2011)
This research aims to study the Brazilian educational public policies, focusing the Inclusive Education, some international statements, and their influences on the Brazilian Inclusive Education found in Guiding Curricula of Curitiba from year 2000 up to 2009. Besides, this study intends to focus the story of either the Brazilian educational process, or those inclusive educational policies during the year of 2009 in Curitiba. These analyzes are important for the establishment of the perception of different ways of social, political, and economic relations due to the educational issues. This work is produced by the use of the historical dialectic materialism so that one shall not deviate from the main point. This study consists of six parts. The first chapter tells about the Brazilian educational process. In chapter two, public policies on the Inclusive Education for the handicapped between the years of 1990 up to 2010 are deepened. In chapter three, the Inclusive Education in the Brazilian Public Policies is analyzed. In chapter four, a discussion on the Inclusive Education inside the neo-liberalism context is provided. The chapter five deals with the 1996 Basic Curriculum to the 2009 Guiding Curricula in Brazil.